Fenomena Baganyi bagi Masyarakat Minangkabau Kontemporer: Studi Gender di Nagari Panampuang, Sumatera Barat - Siadio, Sidiq; Sahmat, Muhd Syahazizamir (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
This article examined the practice of baganyi in Minangkabau society, particularly in Nagari Panampuang Ampek Angkek District, which referred to the act of a husband leaving his wife’s residence without clear legal or marital resolution. The study aimed to analyze the social and customary meanings of baganyi, its impact on women’s rights, and efforts to integrate customary law with Islamic law in addressing this practice. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews and documentation involving perpetrators of baganyi, abandoned wives, customary leaders, and community figures. The findings indicated that baganyi was interpreted as a customary mechanism for resolving domestic conflicts. However, this practice often neglected principles of gender justice and failed to provide adequate legal protection for women. Conflict resolution that relied excessively on customary mechanisms without synergy with Islamic law and formal legal institutions tended to perpetuate structural inequalities against women. The study implied the need for an integrative approach that combined customary values, sharia principles, and formal legal protections in order to establish a system of domestic conflict resolution that was just, humane, and civilized.